Chemomechanical caries removal methods: A literature review - Manal S. Maashi; Heba M. Elkhodary; Najlaa M. Alamoudi; Nada O. Bamashmous (Elsevier, 2023)
Aim: To provide dental practitioners and researchers with a comprehensive review of the historical development, chemical composition, mechanisms of action, advantages, and drawbacks of different chemomechanical caries removal (CMCR) agents. Methods: An electronic search was performed for all articles published on CMCR agents in various databases, including the Web of Science, PubMed, Cochrane, Scopus, and Google Scholar bibliographic databases, from January 1, 1975, to July 31, 2022. Results: Records were identified using the following search terms: Brix3000, Carie-Care, Caridex, Carisolv, chemomechanical caries removal, conventional surgical method, and Papacárie. A total of 171 articles were screened based on the titles and abstracts, of which 126 were deemed eligible for inclusion after duplicates were removed. Following a manual search of the reference list, eight articles were added. Articles were then excluded for other reasons, such as being written before 1975, being written in a language other than English, and the non-availability of the full text. Overall, 120 articles were included in the analysis (literature reviews [n = 27], systematic reviews [n = 8], research articles [n = 82], case reports [n = 3]). Conclusion: CMCR is a potential method of caries control in the future as an alternative to the conventional surgical approach in standard dentistry applications. It is more widely accepted, less painful, and has comparable efficacy to the conventional surgical method. Clinical significance: A continuous trend among manufacturers has been observed since 1975 to reduce the drawbacks of CMCR agents. Moreover, evidence-based minimally invasive techniques, including CMCR agents that require minimal or no aerosol-generating procedures, are preferred while measures to control the spread of coronavirus disease are in force.